2014
DOI: 10.1038/bmt.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and viral infections after allogeneic hematopoietic transplantation from unrelated donors in adults: improving outcomes over time

Abstract: Umbilical cord blood (CB) is increasingly used as an alternative source of stem cells in adult unrelated transplantation. Although registry studies report similar overall outcomes in comparison with BM/PB, comparative studies focusing on severe infections and infection-RM (IRM) with a long follow-up are scarce. A total of 434 consecutive unrelated transplants (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) were retrospectively analyzed to compare overall outcomes, incidence and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…However, other transplant‐related factors as the incidence of GVHD (not addressed in this study) could also play a role in the incidence of IMI in this population. Contrary to other studies, we did not observe a higher incidence of IMI in patients receiving more immunosuppressive transplant modalities such as CD34+ selection or cord blood . While it is possible that the more aggressive prophylactic approach used at our center may overcome a higher risk for mold infections in patients receiving highly immunosuppressive transplant modalities, this would need to be confirmed in comparative studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, other transplant‐related factors as the incidence of GVHD (not addressed in this study) could also play a role in the incidence of IMI in this population. Contrary to other studies, we did not observe a higher incidence of IMI in patients receiving more immunosuppressive transplant modalities such as CD34+ selection or cord blood . While it is possible that the more aggressive prophylactic approach used at our center may overcome a higher risk for mold infections in patients receiving highly immunosuppressive transplant modalities, this would need to be confirmed in comparative studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, a study from Massachusetts General Hospital did not show a correlation between prior fungal infection and invasive fungal disease 14 . Parody and colleagues reported a higher incidence of invasive aspergillosis after UCBT but no difference in mortality compared to MUD 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple trials have demonstrated the safety and efficacy of pre-emptive strategies using oral valganciclovir [15]. However, despite the use of a preemptive strategy, the incidence of CMV disease is still 10% at 1 year following alloSCT in CMV-seropositive patients [16,17], illustrating the need for effective CMV-specific T cell immunity.…”
Section: Introductionmentioning
confidence: 99%